1967
DOI: 10.2466/pr0.1967.20.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Warned Shock: Information and/or Preparation

Abstract: Human Ss preferred warned shock to unwarned shock when the warning signal concained 2 b~ts of information (25% shock) but not when i t was redundant, i.e., 0 bits (100% shock). Rated strength of preference was also related to the information conra~ned in the warning.The research reported here deals with the important role of environmental stimuli or warning signals which make experimental events more predictable.A simple but central question guided our research: Do individuals or organisms prefer to "know" whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…While several studies have investigated the question of the relative aversiveness of sig-37 1973, 20, 37-46 NUMBER I (JULY) nalled vs unsignalled punishment, procedural limitations in two of the studies (Knapp, Kause, and Perkins, 1959, Experiment II;Badia, Suter, and Lewis, 1967) and a source of confounding in the remaining study (Church, 1969, pp. 138-140) prevent an unambiguous interpretation of the findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies have investigated the question of the relative aversiveness of sig-37 1973, 20, 37-46 NUMBER I (JULY) nalled vs unsignalled punishment, procedural limitations in two of the studies (Knapp, Kause, and Perkins, 1959, Experiment II;Badia, Suter, and Lewis, 1967) and a source of confounding in the remaining study (Church, 1969, pp. 138-140) prevent an unambiguous interpretation of the findings.…”
mentioning
confidence: 99%
“…138-140) prevent an unambiguous interpretation of the findings. Thus, Knapp et al (1959, Experiment II) and Badia et al (1967) showed that rats and humans, respectively, would choose signalled over unsignalled shock-punishment; however, in both cases the shock was long delayed following the response and the signal was relatively brief, thus minimizing the role of the signal in bridging the temporal gap between the response and the delayed punisher. It is not clear whether these same effects would have been obtained if the signal of punishment had followed the response immediately and remained on until the shock-punisher occurred; this would have provided a greater degree of association between the response and punishment.…”
mentioning
confidence: 99%
“…对负性刺激, 在不同预测水平上对 CS 所诱发的平均波幅进行预测水平 × 电极点重复测量方差分析。 在 120~180 ms 时间窗口内,电极点的主效应不显著(F(2, 41)= 6.76, p > 0.05, η 2 = 0.05),不同预测水平之 间的差异从 PZ 至 FZ 点,差异逐渐增加大,且差异显著(F(1, 13) = 5.21, p < 0.05, η 2 = 0.24)。电极点与刺 激性质的交互作用不显著(F(2, 41) = 7.56, p > 0.05, η 2 = 0.14)。在 350~450 ms 时间窗,电极点的主效应显 著(F(2, 41) = 1.46, p < 0.05, η 2 = 0.13),预测水平主效应显著(F(1, 13) = 6.48, p < 0.05, η 2 = 0.24)。电极点与 刺激性质的交互作用显著(F(2, 41) = 4.98, p < 0.05, η 2 = 0. (Moberg & Curtin, 2009;Sun et al, 2011;Jin et al, 2013 (Badia, Suter & Lewis, 1967;Lockard, 1965;Pervin, 1963…”
Section: 负性刺激在不同预测水平上的脑电结果unclassified
“…Other researchers have acknowledged the anxiety of occupational therapy students in relation to their fieldwork placements, but rather than researching the construct of anxiety they have focused on strategies employed by students to enable them to cope with such anxiety (Madill, Hagler & Mitchell, 1990;, 1993. Previous research has indicated that a new experience is often associated with high state anxiety (Badia, Suter & Lewis, 1967;Collard, 1967;Freud, 1926;Greenstein, 1983;Spielberger, 1972;Tooth, Tonge & McManus, 1989). On the basis of this research it can be assumed that all students who are anticipating fieldwork placement may experience high levels of state anxiety.…”
Section: Introduction Anxietymentioning
confidence: 99%